Aspirin and 5-Aminoimidazole-4-carboxamide Riboside Attenuate Bovine Ephemeral Fever Virus Replication by Inhibiting BEFV-Induced Autophagy - Tseng, Hsu-Hung; Huang, Wei-Ru; Cheng, Ching-Yuan; Chiu, Hung-Chuan; Liao, Tsai-Ling; Nielsen, Brent L.; Liu, Hung-Jen (Frontiers in Immunology, 2020)
Recent study in our laboratory has demonstrated that BEFV-induced autophagy via activation of the PI3K/Akt/NF-κB and Src/JNK pathways and suppression of the PI3K-AKt-mTORC1 pathway is beneficial for virus replication. In the current study, we found that both aspirin and 5-aminoimidazole-4-carboxamide-1--riboside (AICAR) siginificantly attenuated virus replication by inhibiting BEFV-induced autophagy via suppressing the BEFV-activated PI3K/Akt/NF-κB and Src/JNK pathways as well as inducing reversion of the BEFV-suppressed PI3K-Akt-mTORC1 pathway. AICAR reversed the BEFV-activated PI3K/Akt/NF-κB and Src/JNK pathways at the early to late stages of infection and induced reversion of the BEFV-suppressed PI3K-AKt-mTORC1 pathway at the late stage of infection. Our findings reveal that inhibition of BEFV-induced autophagy by AICAR is independent of AMPK. Furthermore, we found that AICAR transcriptionally downregulates the ATG related genes ULK1, Beclin 1, and LC3 and enhances Atg7 degradation by the proteasome pathway. Aspirin suppresses virus replication by inhibiting BEFV-induced autophagy. It directly suppressed the NF-κB pathway and reversed the BEFV-activated Src/JNK pathway at the early stage of infection and reversed the BEFV-suppressed PI3K/Akt/mTOR pathway at the late stage of infection. The current study provides mechanistic insights into the effects of aspirin and AICAR on BEFV replication through suppression of BEFV-induced autophagy.